The Involvement of Parent on the Educational Achievement of Low-Performing Students: Basis for Restrengthening their Roles to Unlock the Students’ Academic Potential - Sanchez, Kinsan (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the level of parental involvement and its relationship to the academic performance of low-performing students at Gat Andres Bonifacio High School during the School Year 2024–2025. Grounded in Ecological Systems Theory and Epstein’s framework, the study analyzed parental involvement across six dimensions: parenting, communication, volunteering, learning at home, decision-making, and community collaboration, and determined differences based on demographic characteristics such as number of children, educational attainment, family income, and employment status. A quantitative descriptive–comparative research design was employed, involving 288 parent-respondents selected through purposive sampling from a population of 1,129 students. Data were gathered using a modified and validated parental involvement questionnaire and analyzed using descriptive statistics (frequency, percentage, and mean) and inferential statistics through One-way Analysis of Variance (ANOVA). Results revealed that overall parental involvement was slightly involved (composite mean = 2.49), with moderate engagement in communication, learning at home, and decision-making, and lower involvement in parenting, volunteering, and community collaboration. Significant differences were found across all dimensions when grouped according to demographic variables (p = .000), with higher educational attainment, stable employment, and higher income associated with greater involvement. The study concludes that parental involvement remains limited and is significantly influenced by socioeconomic and demographic factors, affecting students’ academic outcomes. It recommends targeted school-based interventions and parent development programs to strengthen engagement and improve learning outcomes. The study aligns with SDG 4 (Quality Education), SDG 10 (Reduced Inequalities), and SDG 17 (Partnerships for the Goals) by addressing educational disparities and promoting collaborative support systems. It contributes to educational and socio-economic sustainability by informing policies and practices that enhance school–home partnerships and equitable student development.
Keywords: Academic Performance; Demographic Profile; Low-Performing Students; Parental Involvement; School-Based Management; Socioeconomic Factors